IMPROVEMENT IN LABORATORY REARING OF IMMATURE STAGES OF SNAIL-KILLING FLY SEPEDON SPHEGEA (FABRICIUS) AND THEIR SURVIVAL (INSECTA, DIPTERA, SCIOMYZIDAE) - S.Tirgari; J.Massoud (Tehran University of Medical Sciences, 1978)
The biology of immature stages of S.sphegea and different techniques for their laboratory rearing has been studied during the past five years (1972-77). This fly is one of the 18 Iranian species of snail-killing flies which is dominant in the focus area of schistosomiasis (Khuzestan Province) in the south-west of Iran. The following procedures improved appreciably our laboratory rearin-technics and greatly reduced larval mortality: 1- Large number of fresh aquatic snails required for the progress of this study has been obtained at the entrances of the traditional under ground water canals (Ghanat) in Teheran. These canals are almost permanent sources of snails because their water temperatures are rather constant through out the year and the water is by far protected from the surface pollution. In other cases, fresh snail was brought from distant swamp and rice fields. Attempts to maintain and to rear live aquatic snails, in large container equipped with aeration pump were not successful due to infection with coli form bacteria. Although the infected snails did not show any biological ill symptoms, could cause heavy mortality among larvae of flies. 2- Fly larvae were reared in plastic container of 28×32 cm. containing 7 to 8 liters of water (7 to 8 cm.depth). Eight to 12 laboratory vials filled with water were placed vertically in several rows in each container to secure uniform distribution of both snails and fly larvae. Fresh and dried leaves of lettuce were used to feed the snails. 3- Dead snails and their shells were picked out by forceps and half of the volume of water of all containers was drained from the bottom by siphoning every two days. 4- The surface pollution of water in the containers, which caused high mortality in different stages of larval development, was removed every four to five days by strips of blotting paper. The oily missed pollution on the water-surface was mostly due to dead snails, rotten leaves of lettuce and to a lesser extend caused by air pollution. 5- Several floating sticks on the inner periphery of each container provided resting place mostly for full-grown larvae. Many of the third stage larvae used to craw1 out of the containers, and sometimes suffering more than 50% mortality. The average survival of newly borne larvae up to pupal stage in 4 cohort of 15 was 71.7, whereas the average survival of 24 hours-fed larvae on crushed snail prior to release, in 5 cohort reached to 84% (min. 66. 66, max. 100%). It is concluded that the feeding of newly borne larvae on crushed aquatic snails for 24 hours prior to release is advantageous, in case of biological based on the mass release of larvae of the above snail-killing fly.